Othello - Honigmann, E.A.J. (Humanities Press International, 1997)
This edition sheds new light on the text of the play as we have come to know it, and on our knowledge of its early history. Honigmann examines the thematic portrayal of feminism, morality, and otherness. He provides a general character criticism, but delves more deeply into Othello, Iago, Desdemona, and Emilia in individual sections. He discusses the play in performance and the relationship between reading it and seeing it. He also explores topics such as its date, sources, and the conundrum of "double time"